Catheter-related atrial thrombus: tip of the iceberg?. (19th February 2015) - Dilek, Melda; Kaya, Coskun; Karatas, Ahmet; Ozer, Ismail; Arık, Nurol; Gulel, Okan
Abstract: Although guidelines recommend catheters as a last resort for establishing a vascular access in patients undergoing dialysis, they continue to be used widely for this purpose. Catheter-related atrial thrombus (CRAT) is rarely reported in this group of patients, and it can lead to serious complications. The aim of this study was to determine the incidence of CRAT in patients undergoing hemodialysis with permanent-tunneled catheters. A total of 50 patients undergoing hemodialysis with permanent catheters were included in this study. The diagnosis of CRAT was based on transthoracic echocardiography findings. Thrombus was present in nine patients (18%) and related to the tip of the catheter in all cases. Except for one patient with two foci of thrombus, all patients had a single focus. There were no significant associations between the development of thrombus and the duration of catheter use or the location of the catheter. Furthermore, catheter-related atrial thrombus did not appear to have a significant effect on mortality. The asymptomatic character of CRAT can be responsible for the low reporting rates, and its exact role in increased mortality and morbidity related with catheter use remains unknown. While planning management strategies, information on different options for vascular access routes and possible catheter-related complications should be provided to all patients who will undergo dialysis, together with a discussion involving other replacement alternatives for end-stage renal disease.